Synthesis of conformationally locked analogs of quinolin-6-yloxyacetamide fungicides. Issue 49 (7th December 2016) - Murphy Kessabi, Fiona; Beaudegnies, Renaud; Quaranta, Laura; Lamberth, Clemens
Graphical abstract: Highlights: Three different methods for the synthesis of conformationally locked quinoil-6-yloxyacetamide fungicides are described. The O, S-acetal of the lead compounds has been tied back to the adjacent quinoline positions 5 or 7. First examples with a [1, 3]oxathiano[6, 5- g ]quinoline scaffold are described. First examples with a [1, 3]oxathiocino[6, 7- f ]quinoline scaffold are described. Abstract: Three different synthesis pathways delivered novel tricyclic compounds which are conformationally locked analogs of quinolin-6-yloxyacetamide fungicides by cyclization of their acetal or O, S-acetal function to quinoline positions 5 or 7. Examples of the fused ring systems of [1, 3]oxathiano[6, 5- g ]quinoline and [1, 3]oxathiocino[6, 7- f ]quinoline, which have been unknown to the chemical literature before, are herein reported for the first time.